2020 International Congress on Human-Computer Interaction, Optimization and Robotic Applications (HORA) 2020
DOI: 10.1109/hora49412.2020.9152831
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Automation and Robotics for High Volume Labour-Intensive Manufacturing

Abstract: High volume, labour-intensive manufacturing operations pose several challenges for successful operations. It is an even bigger challenge to move away from manual dependency and shift towards automation of production processes. There seems to be no general agreement among researchers on what are the critical success factors (CSFs) on the implementation of advanced automation and robotics processes in the manufacturing environment. Success factors vary across the manufacturing industry and also organizational un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Clear communication of decisions concerning resource allocation can increase stakeholders' acceptance. Lai et al [49] identified critical success factors when implementing advanced automation and robotics processes within the manufacturing industry, suggesting further actions for senior management to show support. These actions include having a good understanding and knowledge of the introduced robotic system and automation implementation and providing leadership to workers (either directly or through delegation of authority) to ensure smooth project implementation and organizational members' cooperation.…”
Section: Management Supportmentioning
confidence: 99%
“…Clear communication of decisions concerning resource allocation can increase stakeholders' acceptance. Lai et al [49] identified critical success factors when implementing advanced automation and robotics processes within the manufacturing industry, suggesting further actions for senior management to show support. These actions include having a good understanding and knowledge of the introduced robotic system and automation implementation and providing leadership to workers (either directly or through delegation of authority) to ensure smooth project implementation and organizational members' cooperation.…”
Section: Management Supportmentioning
confidence: 99%